Automated experimental complex on the platform of modern ASCME - Omorov Turatbek; Asiev Abai; Osmonova Rima; Takyrbashev Beishenaly; Imanakunova Zgenishkul; Suerkulov Manas (E3S Web of Conferences)
Currently, in order to automate and digitalize processes in electrical distribution networks (DEN), ASCME software and hardware systems are widely used, which are mainly designed to solve problems of commercial electricity metering. At the same time, these automated systems do not solve such urgent problems as optimizing the operating modes of distribution networks, operational monitoring of technical and commercial losses of electricity, as well as diagnosing network conditions, including localizing the coordinates of unauthorized withdrawals of electricity (UWE). To date, the National Academy of Sciences of the Kyrgyz Republic and a number of foreign scientific centers have developed the scientific foundations and technologies for solving the above problems in real time. In order to test and study the effectiveness of these new results, it is advisable to create an automated experimental complex (AEC), which is essentially a physical model of ASCME. This is due to the fact that the use of automated information systems currently used in distribution networks for this purpose is practically impossible. This article discusses the general structure, functional tasks and main directions of research using AEC. The complex includes a physical model of the distribution network and the main functional elements of modern automated control and accounting systems for electricity (ASCAE), such as a data concentrator, a computer server, single-phase and three-phase electricity meters and a telecommunications module for transmitting and receiving data. The basis of the special software of the experimental complex is made up of new methods and technologies for solving the above functional problems, which are not included in modern AMR systems. AEC is planned to be used not only for conducting scientific research and experiments, but also for the educational process in technical universities with areas of training in the electrical power industry.